Exploration of Affect and Antecedent Experiences in Non-suicidal Self-injury - (:unkn) unknown (My University, 2017)
Background: Non-suicidal self-injury (NSSI) is defined as deliberate self-harm, without the intention of suicide, causing direct destruction of body tissue (Nock & Favazza, 2009). Individuals with NSSI have significantly increased risk of suicide completion compared to individuals who do not engage in NSSI (Cooper et al., 2007). Therefore, understanding this behavior and the experiences that underlie it are of critical importance. Objective: Current conceptualization of NSSI includes four distinct functions described as the Four Factor Model of NSSI (FFM; Nock and Prinstein, 2004). The present study aims to investigate the distinction between the two automatic (intrapersonal) functions of NSSI described with the FFM- Automatic Negative Reinforcement (ANR) and Automatic Positive Reinforcement (APR). More specifically, the study aims to investigate evidence to support the Automatic Positive Reinforcement subtype. Method: We utilized online survey to recruit participants with clinically significant NSSI. Participants rated experiences of positive and negative affect before and after self-injury for NSSI associated with ANR and APR. These patterns of affect were compared to examine support for the APR subtype. Results: We failed to find support for a distinct APR subtype characterized by significant increases in positive affect or that significantly differed from traditional ANR. A possible subgroup of individuals endorsing “because you were feeling numb or empty” who report low antecedent affect may indicate initial support for APR that requires further follow-up. Conclusions: Implications for the APR and FFM are discussed. Alternative perspectives and future directions for research are also reviewed.
Keywords: Affect; Automatic Negative Reinforcement; Four Factor Model; Nssi